Análisis de los hechos económicos en la conciliación fiscal que afectan las cuentas de orden fiscal y el reconocimiento del impuesto diferido de renta. (2013)
The purpose of this text is to elaborate an analysis of the economic facts that affect the fiscal order accounts and the tax deferred from revenue for which it demands a special treatment between the countable and the fiscal order. For the development of this task we start by identifying the temporary differences that must be taken into consideration in the accounts of order and that affect on the recognition of the deferred liabilities, debit and credit. The balance in the dynamic of the accounts is described, like the accounts that are affected in this conciliation process between the countable and the fiscal that face a company or an economic entity.